Seasonal and Diurnal Variations of Observed Convective Rain Events in Metro Manila, Philippines - Bañares, Erica N (Archīum Ateneo, 2021)
The seasonal and diurnal characteristics of localized convective rain events in Metro Manila, Philippines were examined using observations from 16 automated weather stations in the city during the years 2013–2014. After partitioning total rainfall to determine the proportion that is mainly due to localized convection, the diurnal patterns of frequency and intensity of convective rain were then investigated during the northeast monsoon (from November to March), summer (from April to May), and southwest monsoon (from June to October) seasons. Maximum changes in meteorological variables were used to further verify and characterize localized convective rain events over the city. Results show higher rainfall (by ~500 mm) over northern Metro Manila compared to the southern area throughout the period of study. Although total rainfall was highest during the southwest monsoon season, it was during the summer season, when the total rainfall was least, that the largest proportion of rainfall, i.e. 55%, was attributed to convective rain. Almost 45% of the total convective rain events were identified as localized rain events. During the summer season, localized convective rain events in Metro Manila were prominent and vigorous (i.e. greater change in meteorological variables) in the afternoon, and were noted to move along the direction of the prevailing wind, i.e. from the northeastern side of the city towards the west. Increased understanding of the meteorological characteristics of these localized rain events can help improve rainfall forecasting over Metro Manila, leading to better disaster risk reduction and resilience in the city.